Karakteristik Uji Marshall Campuran Laston (Ac-Wc) Dengan Abu Bata Dan Semen Sebagai Bahan Pengisi (Filler) - Ary Iqbal; Muhammad Shalahuddin; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Housing development has led to increase in the demand for the production of non-structural constituent materials such as bricks. Apart from that the increased production of bricks also creates waste from thebricks themselves such as defective brick. The defect may caused by improper forms, inadequate requirements for combustion and broken stones when transporting locations. This study aims to find theMarshall characteristic value in the asphalt concrete wearing course mixture filler under conditions of optimum asphalt content with used variations of brick ash and portland cement as filler replacement withratio of 0:100, 25:75, 50:50, 75:25 and 100:0. The method used in this study is the experimental method and descriptive analysis. The combination of these two methods identified based on facts obtained during testing and then analyzed based on literature and other supporting data. In the condition of optimum asphaltcontent, all variations meet the Marshall characteristics requirements. The best composition is found in variations of 100:0 (100% brick ash : 0% portland cement) with a stability value of 1280 kg and flow of 3.90mm, with optimum asphalt content of 5.90% and VMA value of 16.00%, VFA 75.00%, VIM 3.95% and MQ 345 kg/mm.Keywords: Brick Ash, Laston AC-WC, Filler